Cutaneous Metastasis of Gestational Trophoblastic Neoplasia on The Face - Shahid, Ruqaiya (International Journal of Pathology, 2019)
Background: Choriocarcinoma is a malignant tumor of trophoblastic origin which is highly sensitive to chemotherapy and has a 95-98 % 5-year survival rate even after metastasis. Objective: We report a rare site of cutaneous metastatic choriocarcinoma in a 30 years old lady who presented with multiple bleeding nodules on her face. Case Report: The patient had a history of vaginal delivery one and a half year back and presented to the hospital with abnormal uterine bleeding for three months. The skin biopsy revealed a tumor showing dual cell population of cytotrophoblasts and syncytotrophoblasts with extensive hemorrhage and necrosis. Tumor cells were positive for immunohistochemical stains cytokeratin and beta Human Chorionic Gonadotrophin (βHCG) confirming the trophoblastic origin. Her β HCG level was 31,550mIU/ml. Metastatic Gestational Trophoblastic Neoplasia (GTN) occurs in 4 % of patients after evacuation of complete hydatidiform mole and very infrequently after other pregnancies. Lung (80%), vagina (30%), brain (20%) and liver (10%) are common sites of metastasis. Conclusion: Cutaneous metastasis in GTN has been reported in only 13 other patients till 2015. Our report highlights the importance of histo-pathological input in determining site of primary malignancy. Overall cutaneous metastasis is a poor prognostic indicator for survival